Natural convection flow in porous enclosures with heating and cooling on adjacent walls and divided by a triangular massive partition - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Loan (Pergamon-Elsevier Science Ltd, 2008)
The problem of steady, laminar, natural convection flow in a porous enclosure divided by a triangular massive partition has been formulated. The massive triangular partition is a solid adiabatic body which is located to the right and top wall. Bottom and left vertical wall of porous enclosure are isothermally heated and cooled, respectively. Remaining wall is adiabatic. Governing equations using Darcy model are solved numerically by the finite-difference method and the Successive Under Relaxation (SUR) technique is used to solve linear algebraic equations. Thanks to massive partition, two different enclosure are formed, depends on dimensions of the triangular body, as triangle and trapezoidal. Flow patterns and temperature distributions were presented at different aspect ratios (0 <= AR <= 1) and Rayleigh numbers (100 <= Ra <= 1000). Results are given for different aspect ratios (AR) for AR= 0, 0.25, 0,50, 0.75 and 1. A parametric study is conducted and a set of representative results for flow and temperature characteristics are presented and discussed. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: natural convection; porous enclosure divided by triangular portion; numerical solution